2018
DOI: 10.1002/chem.201802286
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding of N‐Heterocyclic Carbenes in Solution: Mechanisms of Solvent Reorganization

Abstract: The hydrogen-bond dynamics of N-heterocyclic carbenes plays a central role in their proton-transfer reactions, and the effects of hydrogen bonding are also often invoked in corresponding organocatalytic applications. In the present study, the structures and lifetimes of hydrogen bonds have been investigated for several carbenes in alcohol-containing solutions by classical molecular dynamics simulations. The basicity of the carbene was found to be of major importance; while the least basic carbenes are often in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…The high basicity of NHCs makes them also strong hydrogen bond acceptors, a feature that has been suggested first by Wanzlick, and evidenced later by theoretical calculations and experiments . This is also in accordance with the observations that solvent rearrangement—that is, the exchange of a hydrogen bond donor at the basic site of the NHC (Figure )—is the rate limiting step of H/D exchange reactions of azolium cations.…”
Section: Basicity Of N‐heterocyclic Carbenessupporting
confidence: 87%
See 2 more Smart Citations
“…The high basicity of NHCs makes them also strong hydrogen bond acceptors, a feature that has been suggested first by Wanzlick, and evidenced later by theoretical calculations and experiments . This is also in accordance with the observations that solvent rearrangement—that is, the exchange of a hydrogen bond donor at the basic site of the NHC (Figure )—is the rate limiting step of H/D exchange reactions of azolium cations.…”
Section: Basicity Of N‐heterocyclic Carbenessupporting
confidence: 87%
“…Through molecular dynamics simulations we have observed that the exchange of a solvent molecule, which is in hydrogen bond with the NHC, does not necessitate the formation of the free NHC in the solution . Instead, the single lone pair can accommodate a second hydrogen bond donor, allowing for an associative exchange, which can facilitate the hydrogen bond dynamics—thus the solvent exchange—of NHCs (Figure ).…”
Section: Alternative Reaction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in protic (hydrogen bonding) solvents the dissociative mechanism can be rationalized as a substitution of the ammonium cation by the solvent at the hydrogen bond acceptor hypovalent carbon atom, followed by the reaction depicted in Figure . Such exchange of hydrogen bond donors at NHCs has been discussed before, and has been found to depend on steric effects and the hydrogen bond acceptor strength of the NHC in its rate and mechanism . The reaction of the solvent–NHC hydrogen‐bonded complex with the substrate (Figure ) can be considered as a special case of the associative mechanism depicted in Figure .…”
Section: Resultsmentioning
confidence: 91%
“…However, hydrogen bonding can also have a tremendous effect on the availability of the free NHC. NHCs are highly basic compounds, and hence they can form very strong hydrogen bonds, which can result in a stabilization up to even 10–20 kcal mol −1 . Although the stabilization by hydrogen bonding activates the aldehyde substrate, it may also occupy the NHC lone pair, which is the very site, to which the electrophilic substrate should bind in the reaction.…”
Section: Resultsmentioning
confidence: 99%